Islamic Digital Wellbeing: An Islamic Education Perspective on Overcoming FOMO in Generation Z: Kesejahteraan Digital Islami (Islamic Digital Wellbeing): Perspektif Pendidikan Islam dalam Mengatasi FOMO pada Generasi Z - utami, hawa; niswah, luthfiyatun; rochmat, Cecep; dewi, Mutiara (ABHATS: Jurnal Islam Ulil Albab, 2026)
The Fear of Missing Out (FOMO) phenomenon, widely experienced by Generation Z, arises from excessive social media use and a lack of spiritual balance in digital life. This condition leads to anxiety, dependency, and psychological imbalance, which negatively impacts the quality of life. To address these issues, this study aims to formulate an Islamic Digital Wellbeing model as a conceptual approach to reducing FOMO by integrating Islamic values and digital psychology theories. This study employs a Library Research method, examining various Islamic literature, modern psychology, and digital wellbeing theories to construct a comprehensive conceptual model. The results indicate that Islamic values such as wasathiyyah (balance), tazkiyah an-nafs (purification of the soul), adab (etiquette), and ihsan (spiritual awareness) serve as the primary foundation for Islamic digital wellbeing. The resulting model consists of five aspects: digital tazkiyah, niyyah and maqasid, digital adab, ihsan connectivity, and digital wasathiyyah. These aspects play a crucial role in helping Generation Z manage technology use proportionally, meaningfully, and as a form of worship. Based on these findings, this study suggests that the Islamic Digital Wellbeing model be implemented in character education, Islamic digital literacy, and youth development programs, while also serving as a basis for further empirical research in the educational and social fields. [Fenomena Fear of Missing Out (FOMO) yang banyak dialami oleh Generasi Z muncul akibat penggunaan media sosial yang berlebihan dan minimnya keseimbangan spiritual dalam kehidupan digital. Kondisi ini memunculkan kecemasan, ketergantungan, serta ketidakseimbangan psikologis yang berdampak pada kualitas hidup. Untuk menjawab persoalan tersebut, penelitian ini bertujuan merumuskan model Islamic Digital Wellbeing sebagai pendekatan konseptual dalam mengurangi FOMO dengan mengintegrasikan nilai-nilai Islam dan teori psikologi digital. Penelitian ini menggunakan metode Library Research dengan menelaah berbagai literatur keislaman, psikologi modern, dan teori kesejahteraan digital untuk menyusun model konseptual yang komprehensif. Hasil kajian menunjukkan bahwa nilai-nilai Islam seperti wasathiyyah (keseimbangan), tazkiyah an-nafs (penyucian jiwa), adab, dan ihsan (kesadaran spiritual) menjadi dasar utama terbentuknya kesejahteraan digital Islami. Model yang dihasilkan terdiri atas lima aspek, yaitu tazkiyah digital, niyyah dan maqasid, adab digital, ihsan connectivity, dan wasathiyyah digital, yang berperan dalam membantu Generasi Z mengelola penggunaan teknologi secara proporsional, bermakna, dan bernilai ibadah. Berdasarkan hasil tersebut, penelitian ini menyarankan agar model Islamic Digital Wellbeing diimplementasikan dalam pendidikan karakter, literasi digital Islami, serta program pembinaan remaja, sekaligus menjadi dasar penelitian lanjutan untuk pengujian empiris di bidang pendidikan dan sosial.]